THE IMPLEMENTATION OF PACTA SUNT SERVANDA PRINCIPLE AS A BASIS FOR MAKING MEMORANDUM OF UNDERSTANDING - Arum Puspita Kesuma; Muh Afif Mahfud (Awang Long Law Review, 2023)
Memorandum of Undersatanding is an initial agreement that regulates and provides an opportunity for the parties to conduct a feasibility study before arriving at a more comprehensive agreement. Making a Memorandum of Undersatanding requires the implementation of the principle of pacta sunt servanda to show that the parties have a binding agreement with each other. This research aims to find out how the implementation of pacta sunt servanda principle as the basis for making Memorandum of Undersatanding and how the legal position of Memorandum of Undersatanding. Using normative juridical legal research method with qualitative analysis. The results of this study conclude that the implementation of the principle of pacta sunt servanda as the basis for making Memorandum of Undersatanding is very important to ensure that the parties fulfill their promises and commitments and the agreement is respected and fulfilled by the parties. The legal position of the Memorandum of Understanding from the perspective of contract law is as an informal agreement that is not legally binding, but has strategic and diplomatic importance.